63.5k views
0 votes
So for the variable. leave your answer in its exact form

So for the variable. leave your answer in its exact form-example-1

1 Answer

5 votes

Step-by-step explanation


2e^(3-3x)+7=31

Step 1

subtract 7 in both sides


\begin{gathered} 2e^(3-3x)+7-7=31-7 \\ 2e^(3-3x)=24 \end{gathered}

Step 2

divide both sides by 2


\begin{gathered} 2e^(3-3x)=24 \\ (2e^(3-3x))/(2)=(24)/(2) \\ e^(3-3x)=12 \end{gathered}

Step 3

get the ln in both sides


\begin{gathered} \ln (e^(3-3x))=\ln (12) \\ 3-3x=2.48 \\ \text{subtrac 3 in both sides} \\ 3-3x-3=2.48-3 \\ -3x=\ln (12)-3 \\ \text{Divide both sides by -3} \\ (-3x)/(-3)=(\ln (12)-3)/(-3) \\ x=(\ln (12)-3)/(-3) \end{gathered}

User Rinku Choudhary
by
4.7k points